ANALYSIS OF THE ROLE OF TRADITIONAL MARKETS IN IMPROVING THE COMMUNITY'S ECONOMY FROM AN ISLAMIC ECONOMIC PERSPECTIVE IN SIPIONGOT VILLAGE, NORTH PADANG LAWAS - Salmi Pane; Zuhrinal M Nawawi; Aqwa Naser Daulay (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research aims to determine the role of traditional markets and the role of the community in improving the economy from an Islamic economic perspective in Sipiongot Village, North Padang Lawas. The method used in this research is a qualitative method with a descriptive approach. The samples used in this research were local government, traders and market visitors. This research uses interview, observation and documentation techniques. The results of the research show that the traditional market in Sipiongot village has the potential to improve the community's economy. The potential of the traditional market in Sipiongot village is firstly, the turnover or income of traders in the traditional market is an average of 400 million per week. Second, the circulation of money in the traditional market in Sipiongot village is approximately 1.6 billion per month